(3GdefjI hGdCed aj TQM Gdedd hGdfMds - (3CMeO Hf jMji Hf GdeQJVj GdRjOj,J (B840 (3g` s
(3ChdgG (B:s
(3Ef CLd GdKfG jbeQ Yf hUa LdGdc hCYXe GdNVhY jbd Yf ELdGdc s
(3BNQgG (B:s
(3agPg GdebGdGJ s
(3GdefjI hGdCed ai TQM cJGH Gdedd hGdfMd hgh GdLRA GdChd ef cJGd ZGjGJ GdCacGQ hfgGjGJ GdCfXGQ GdeMjWI HYLGFH GdHMQ GdRcGQs
(3WHY ef gPG GdcJGH GdbSe GdNGU HWHbGJ GdeYJRdI ai OGFQI GdeYGQa GdYKeGfjI HMjOQ CHGOs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQM s
Keywords: (3GdJhMjO hGdedd hGdfMds